Anatomical Characteristics and Variation Mechanisms on the Thick-Walled and Dwarfed Culm of Shidu Bamboo (Phyllostachys nidularia f. farcta) - Wang, Yujun; Qiao, Guirong; Xu, Jing; Jin, Kangming; Fan, Minyuan; Ding, Yulong; Wei, Qiang; Zhuo, Renying (Frontiers in Plant Science, 2022)
Stable culm variants are valuable and important material for the study of culm development in bamboo plants. However, to date, there are few reports on the mechanism of variation of these bamboo variants. Phyllostachys nidularia f. farcta (Shidu bamboo) is a bamboo variant with stable phenotypes such as a dwarf culm with a thickened wall. In this study, we systematically investigated the cytological characteristics and underlying mechanism of morphological variation in culms of this variant using anatomical, mathematical statistical, physiological, and genomic methods. The anatomical observation and statistical results showed that the lateral increase of ground tissue in the inner layer of culm wall and the enlargement of vascular bundles are the anatomical essence of the wall thickening of Shidu bamboo; the limited elongation of fiber cells and the decrease in the number of parenchyma cells longitudinally are probably the main causes of the shortening of its internodes. A number of genes involved in the gibberellin synthesis pathway and in the synthesis of cell wall components are differentially expressed between the variant and its prototype, Ph. nidularia, and may play an important role in determining the phenotype of internode shortening in Shidu bamboo. The decrease in gibberellin content and the content of the major chemical components of the cell wall of Shidu bamboo confirmed the results of the above transcriptome. In addition, the variation in culm morphology in Shidu bamboo had little effect on the volume of the culm wall of individual internodes, suggesting that the decrease in the total number of internodes and the decrease in dry matter content (lignin, cellulose, etc.) may be the main factor for the sharp decline in culm biomass of Shidu bamboo.